A new species of Noblella (Amphibia: Strabomantidae) from the western slopes of the Andes of Ecuador - Guayasamin, Juan M.; Terán-Valdez, Andrea (Zootaxa, 2009)
We describe a new species of Noblella from the western slope of the Ecuadorian Andes. The new taxon is distinguished from all other species in the genus by lacking dorsal marks (i.e., interobital bar, scapular and sacral chevrons) and by having a bright orange venter. The new species and Noblella heyeri are the only species of Noblella reported in the Pacific Andean versant. We provide an osteological description of the new species and a key for the species in Noblella.